2021
DOI: 10.1002/cssc.202002916
|View full text |Cite
|
Sign up to set email alerts
|

The Misconception of Mg2+ Insertion into Prussian Blue Analogue Structures from Aqueous Solution

Abstract: Prussian blue analogues (PBAs) are commonly believed to reversibly insert divalent ions, such as calcium and magnesium, rendering them as perspective cathode materials for aqueous magnesium‐ion batteries. In this study, the occurrence of Mg2+ insertion into nanosized PBA materials is shown to be a misconception and conclusive evidence is provided for the unfeasibility of this process for both cation‐rich and cation‐poor nickel, iron, and copper hexacyanoferrates. Based on structural, electrochemical, IR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…The studied PBAs follow different ion insertion mechanisms, as reflected in the shape of the cyclic voltammograms (CVs) in Figure (the potential interval in aqueous solution corresponds to the reversible extraction of one K + per Fe in MHCF). As previously reported, for K-rich K-FeHCF and K-NiHCF samples, a monoclinic-to-cubic phase transformation occurs upon K + deinsertion. , Phase transition potentials correspond to sharp maxima in the differential capacitance versus potential plots (Figure B,D). In this case, diffusion coefficients can be estimated by PITT and EIS methods in more narrow potential intervals compared to K-poor CuHCF and NiHCF materials, where a solid solution pathway is dominant and no lattice rearrangements take place upon Fe oxidation and/or reduction. , The single-phase nature of Fe redox in CuHCF and NiHCF is corroborated by a smooth change in the differential capacitance with potential (Figure A,C).…”
supporting
confidence: 73%
See 3 more Smart Citations
“…The studied PBAs follow different ion insertion mechanisms, as reflected in the shape of the cyclic voltammograms (CVs) in Figure (the potential interval in aqueous solution corresponds to the reversible extraction of one K + per Fe in MHCF). As previously reported, for K-rich K-FeHCF and K-NiHCF samples, a monoclinic-to-cubic phase transformation occurs upon K + deinsertion. , Phase transition potentials correspond to sharp maxima in the differential capacitance versus potential plots (Figure B,D). In this case, diffusion coefficients can be estimated by PITT and EIS methods in more narrow potential intervals compared to K-poor CuHCF and NiHCF materials, where a solid solution pathway is dominant and no lattice rearrangements take place upon Fe oxidation and/or reduction. , The single-phase nature of Fe redox in CuHCF and NiHCF is corroborated by a smooth change in the differential capacitance with potential (Figure A,C).…”
supporting
confidence: 73%
“…Despite the observed exceptionally low K + diffusivities in K-FeHCF, the material shows impressive rate capability with >70% of capacity retention at a 40C discharge rate when operating in a constant current mode (Figure C). Earlier, for the PBA materials used in this study, we reported similarly high capacity retention for operation in an aqueous of K + solutions . It is the superior rate capability of PBA materials that leads to the intuitive conclusion about high diffusivities of alkali ions in PBA structures, which is invalidated in this study (below we provide conclusive evidence that this contradiction is apparent).…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…In the reverse process, the inserted species are de-intercalated from the WO 3 film during the oxidation bias (bleaching), resulting in a decrease of the electrode mass . By comparing the de-intercalation formal potentials of the two concentrations of 0.1 and 0.5 M Al­(ClO 4 ) 3 -PC solution, a shift of ∼30 mV could be observed based on the Nernst equation if Al 3+ is the charge-compensating ion. In contrast, a larger potential transition is obtained in the high-concentration solution, indicating that the counterions are also involved in the charge compensation process .…”
Section: Resultsmentioning
confidence: 99%